2018
DOI: 10.1111/apv.12201
|View full text |Cite
|
Sign up to set email alerts
|

Social capital in a crisis: NGO responses to the 2015 Nepalese earthquakes

Abstract: Two major earthquakes hit Nepal in April and May 2015 causing widespread devastation. Many NGOs, including CARE Nepal, International Nepal Fellowship and Richa Bajimaya Memorial Foundation, responded to the crisis in diverse ways. In the relief phase, the three NGOs faced many challenges as a result of inadequate planning for a large‐scale disaster, including access to information, coordination and inaccessibility. NGOs were able to partly overcome these problems through their ability to draw on social capital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Network operations mechanisms should also empower NGOs and address community sustainability issues and weaknesses (Izumi and Shaw 2012 ). Hillig and Connell ( 2018 ) found that network sustainability depended heavily on past practice, NGO member expertise, and the ability to mobilize social capital (Hillig and Connell 2018 ). For example, a case from the NGO Japan Platform (JPF), an international emergency humanitarian aid organization, found that capacity building was vital for efficient joint NGO alliance emergency assistance (Iizuka 2018 ).…”
Section: Key Ngo Network Sustainability Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Network operations mechanisms should also empower NGOs and address community sustainability issues and weaknesses (Izumi and Shaw 2012 ). Hillig and Connell ( 2018 ) found that network sustainability depended heavily on past practice, NGO member expertise, and the ability to mobilize social capital (Hillig and Connell 2018 ). For example, a case from the NGO Japan Platform (JPF), an international emergency humanitarian aid organization, found that capacity building was vital for efficient joint NGO alliance emergency assistance (Iizuka 2018 ).…”
Section: Key Ngo Network Sustainability Factorsmentioning
confidence: 99%
“…However, this NGO failure to ensure effective practice can result in secondary damage that can add to rather than relieve the problems being faced by the disaster victims (Teets 2009 ; Levie et al 2017 ). Hillig and Connell ( 2018 ) specifically highlighted the lack of adequate coordination between some NGOs after the 2015 Nepal earthquake (Hillig and Connell 2018 ), claiming that as “many just came and distributed tarpaulins and went back” (p. 316), there was a duplication of services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued by scholars that linking social capital has a more vital role in affecting the immediate and mid-term rebuilding process in a disaster context. (Rossing et al, 2010;Atkinson, 2014;Bhandari, 2014;Islam and Walkerden, 2015;Rubin, 2016;Nakazato and Lim, 2017;Vachette et al, 2017;Hillig and Connell, 2018) However, the segregation of social capital into these three categories are at times unhelpful, especially in the immediate aftermath of a major disaster. Due to the disaster, institutions together with structures and networks, were fundamentally compromised.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, another pillar of the theoretical model is based on social support, as it is society that shows approval for many of the NGOs’ initiatives by means of financial funds allocated to these institutions [ 30 ]. In this context, social support is very important because, in the case of catastrophes, obtaining financial resources allows for an immediate response on the entity’s behalf [ 31 ]. From the internal aspect of the business, various studies indicate that relying on the support of superiors and/or colleagues contributes decisively to improve job wellbeing [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%